About Point Strategy And Its Influence Towards Students’ Reading Comprehension - Septia, Winda Ayu; Zulianti, Hajjah; Herlisya, Destia (International Journal Corner of Educational Research, 2022)
This research aimed to know the influence of about point strategy towards students' reading comprehension. The writer used quantitative method and categorized the research as quasi experimental method. The writer used 2 classes for experiment class and control class. Cluster Random Sampling Technique was used in taking the sample. The experiment class consisted of 32 students and control class consisted of 34 students. In collecting the data, the writer used reading comprehension test. To know the influence, the writer used t-test formula. It was found that rcount (3, 73) > rtable (1, 98) in level 5% and rcount (3, 73) > rtable (2, 65) in level 1%. It can be concluded that there was positive influence of About-Point strategy towards students’ reading comprehension.